Hubungan Internasional Global dalam Dunia Yang “Barat” - Endriady Edy Abidin; Asma Amin (Journal of International and Local Studies, 2018)
The field of International Relations (IR) today is parochial in the sense of eurocentrism and inadequate in explaining the recent developments in the field. We need a new reverberated, innovative, and inclusive perspective that reflects the voices, experiences, interests, and identity of all humankind. Global IR established for that reason. Global IR is not meant to be a new universal narration of the „East? but to encourage a new diversity of perspectives in knowledge and authority decentralization to create a more „international? and wider IR academic contributions. In Southeast Asia, the richness of historical, social, and cultural sources might become a starting point for a geoepistemological perspective and also an entrance for a perspective, in the umbrella of Global IR, for seeing deeper the 'reality' and 'what is existing' in this region.